Efficacy of Timolol Maleate (0.5%) in Preventing Rise of Intraocular Pressure (IOP) Post Neodymium: Yttrium Aluminum Garnet (Nd: YAG) Capsulotomy - Iqbal, Nazia; Muzaffar, Waqar; Sarfaraz, Muhammad Haroon; Khan, Saim; Yasin, Ubaid Ullah; Abidin, Farooq Ul (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the efficacy of 0.5% Timolol eye drops in preventing rise of intraocular pressure following Neodymium: Yttrium-Aluminum-Garnet laser posterior capsulotomy.Study Design: Quasi-experimental study.Place and Duration of Study: Outpatient Department of Ophthalmology, Combined Military Hospital Multan Pakistan, from May to Nov 2019.Methodology: Patients presenting with posterior capsule opacification, undergoing elective Neodymium: Yttrium Aluminum Garnet (Nd: Yag) Capsulotomy were enrolled in the study. Patients were alternatively assigned to two groups; group-1 was administered 0.5% Timolol Maleate eye drops, while group-2 was administered placebo natural team eye drops. Intraocular pressure for all the patients was measured at three-time points a). First measurement was baseline intraocular pressure at presentation/before the treatment. Second measurement was 1-hour post laser capsulotomy and third measurement was 3 hours post laser capsulotomy.Results: At 1-hour follow up, the mean intraocular pressure was significantly raised in the patients belonging to control group as compared to treatment group (21.45 ± 8.33 mm Hg vs 15.33 ± 3.37 mm Hg, p